Measuring industry digital transformation with a composite indicator: A case study of the utility industry - Yakymova, Larysa; Novotná, Andrea; Kuz, Vasyl; Tamándl, László (Centre of Sociological Research, 2022)
Climate change, urban sprawl, a global pandemic, and the general trend of digitizing economies are driving the need for digital transformation of utilities. Policymakers of industry digital transformation need some aggregated metric that captures the essence of this multidimensional concept, identifies the pros and cons of current policies, and guides future directions based on cross-country benchmarking. This study develops the Industry Digital Transformation Index for the utility industry (IDTIu) as a composite indicator. IDTIu provides an aggregate score for the digital transformation of the national utility industry based on 31 indicators grouped into 8 sub-indices. IDTIu scores were calculated for 34 European countries based on 2020 data. To avoid the methodological challenges of equal weighting and expert assessments, we applied the original Benefit-of-the-Doubt (BoD) model and its two extensions for the proportion and priority of sub- indices. Our results show that (i) the full flexibility of the original BoD model leads to the expected deficiencies in ranking leaders and assigning zeros to insignificant sub-indices; (ii) BoD model with ordinal sub-index share restrictions does not allow ranking of laggards when IoT, AI, and BDA are ranked as top 3 priorities. Therefore, at the current stage of the digital transformation of utilities, we recommend the BoD model with proportional sub-index share restrictions.
Keywords: digital transformation, composite index, Benefit-of-the-Doubt model, utility industry